Infertility Prevalence and Associated Factors among Women in Seoul, South Korea: A Cross-Sectional Study - Hyun Joo Lee; Jung Yeol Han; Han Zo Choi; Baeg Ju Na (Clinical and Experimental Obstetrics & Gynecology)
Background: Infertility is not only a health problem that affects individuals but also a social problem that affects families, societies, and populations. Recently, although infertility rates have been increasing in Korea, there are few studies on this. This study aimed to investigate the prevalence of infertility among Korean women attempting to conceive and factors associated with this. Methods: This cross-sectional study was conducted from May to November 2019. Participants accessed the website of the Seoul Metropolitan Government, gave their consent to the study, and then answered the questionnaire. A total of 2274 women preparing for pregnancy were recruited and their data were analyzed. Results: Among the 2274 women, 443 (19.48%) were infertile. Of these infertile women, 320 (72.2%) had primary infertility and 123 (27.8%) had secondary infertility. The average period of primary infertility was 1.7 ± 1.1 years, whereas the period of secondary infertility was 2.2 ± 1.5 years. The average age of non-infertile and infertile women was 31.9 ± 3.2 years and 33.2 ± 3.8 years, respectively, a statistically significant difference (p < 0.001). Univariate analysis revealed various risk factors for infertility (educational level, social drinking, insomnia, bulimia, artificial abortion, and spontaneous abortion) that were statistically significant. Employment, anorexia, depression, and irregular menstruation showed a marginal significance. However, in the multivariate logistic regression analysis, age ≥35 years, body mass index ≥23, and a history of artificial abortion were significant risk factors for infertility. Conclusions: This study identified the prevalence of infertility in Seoul and the associated factors of women’s infertility. Further research is necessary to identify clinical and male-specific variables related to infertility. These studies are expected to be of great help to prevent infertility and increase the birth rate.